2018
DOI: 10.1371/journal.pone.0190205
|View full text |Cite
|
Sign up to set email alerts
|

The effects of exercise on hypothalamic neurodegeneration of Alzheimer’s disease mouse model

Abstract: Alzheimer’s disease is a neurodegenerative disorder that affects the central nervous system. In this study, we characterized and examined the early metabolic changes in the triple transgenic mouse AD model (3xtg-AD), and their relationship with the hypothalamus, a key regulator of metabolism in the central nervous system. We observed that the 3xtg-AD model exhibited significantly higher oxygen consumption as well as food intake before reported amyloid plaque formation, indicating that metabolic abnormalities o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
54
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(62 citation statements)
references
References 26 publications
5
54
2
1
Order By: Relevance
“…In the present study, β3AR agonist induced weight loss in both NonTg and 3xTg-AD mice. Food consumption was higher in 3xTg-AD compared to NonTg mice, an observation previously reported in this model (Adebakin et al, 2012;K. Do et al, 2018), and CL-316,243 increased food intake in NonTg mice.…”
Section: β3ar Agonist: a Two In One Strategy To Target Both Metabolicsupporting
confidence: 81%
“…In the present study, β3AR agonist induced weight loss in both NonTg and 3xTg-AD mice. Food consumption was higher in 3xTg-AD compared to NonTg mice, an observation previously reported in this model (Adebakin et al, 2012;K. Do et al, 2018), and CL-316,243 increased food intake in NonTg mice.…”
Section: β3ar Agonist: a Two In One Strategy To Target Both Metabolicsupporting
confidence: 81%
“…However, in the brain, MC4R is involved in anorexigenic, ant-inflammatory, and antiapoptotic effects ( Caruso et al, 2013 ). In addition, AD transgenic mouse model 3xTg-AD showed lower levels of MC4R and AgRP mRNA compared to the control ( Do et al, 2018 ), confirming the important role of MC4R in the development of AD.…”
Section: Genes Associated With Obesity and Neurodegenerative And Neurmentioning
confidence: 62%
“…Hypothalamic gene expression showed higher mRNA expression of genes related to inflammation and apoptosis, as well as lower levels of POMC and NPY-expressing neurons. However, voluntary exercise training reduced apoptosis and increased POMC and NPY-expressing neuronal populations ( Do et al, 2018 ). Early exercise intervention can normalize hypothalamic inflammation, neurodegeneration, and the glucose metabolism in 3xTg-AD model, suggesting that exercise can reduce the progression of dementia and AD ( Do et al, 2018 ).…”
Section: Genes Associated With Obesity and Neurodegenerative And Neurmentioning
confidence: 99%
“…In the current study, increased inflammation in the periphery of AD mice (liver, plasma, and visceral fat) mimics trends of increased hypothalamic expression of glial markers Iba1 and GFAP, as well as pro-inflammatory cytokines (TNF-a and IL-1B), in AD males. Previous studies have also reported increased hypothalamic expression of pro-inflammatory markers in 3xTg-AD male mice at even 12 weeks of age [95]. Additionally, free fatty acids from the consumption of a high fat diet can contribute to hypothalamic inflammation [119].…”
Section: Discussionmentioning
confidence: 93%
“…Other AD rodent models similarly report body weight deficits that become more pronounced with age, as well as decreased body fat, despite similar or even increased food consumption [24,[90][91][92][93][94]. While unclear in clinical populations, findings in mice exhibiting AD pathology suggest that elevated basal metabolic rate (measured by oxygen consumption), rather than increased activity levels, may be contributing to these differences [24,91,92,95]. There are some studies that do show hyperactivity in AD mouse models [93]; however, AD males in the current study did not exhibit increased activity levels in open field testing.…”
Section: Discussionmentioning
confidence: 99%